Immune response to Mycobacterium bovis-an5 infection in genetically selected mice (selection IV-A) - Cavalheiro, Juliana Semim [UNESP]; Trindade, B. C. [UNESP]; Balderramas, H. A. [UNESP]; Haanwinckel, M. C. [UNESP]; Pinto, J. G G [UNESP]; Oliveira, S. L. [UNESP]; Paes, A. C. [UNESP] (FapUNIFESP (SciELO), 2007)
Mice genetically selected for high (H) and low (L) antibody production (Selection IV-A) were used as murine experimental model. The aim of the present work was to evaluate the macrophagic activity and to characterize the immune response in Mycobacterium bovis-AN5 infected mice (3×10 7 bacteria). The response profile previously observed in such strains was not similar to that obtained during M. bovis infection; however, it corroborated works carried out using Selection I, which is very similar to Selection IV-A regarding infection by M. tuberculosis and Bacillus Calmette-Guérin (BCG). Considering bacterial recovery, LIV-A mice showed higher control of the infectious process in the lungs than in the spleen, whereas HIV-A mice presented more resistance in the spleen. With respect to macrophagic activity, hydrogen peroxide (H2O 2) was probably not involved in the infection control since there was an inhibition in the production of this metabolite. Nitric oxide (NO) and TNF-α production seemed to be important in the control of bacterial replication and varied according to the strain, period and organ. Evaluation of the antibody production indicated that the multi-specific effect commonly observed in these strains was not the same in the response to M. bovis. Antibody concentrations were higher in LIV-A than in HIV-A mice at the beginning of the infection, being similar afterwards. Such data were compared with delayed-type hypersensitivity (DTH), which was more intense in HIV-A than in LIV-A mice, indicating that antibody production is independent of the capability to trigger DTH reactions and that cellular and humoral responses to M. bovis antigens show a polygenic control and an independent quantitative genetic regulation. Differences were observed among organs and metabolites, suggesting that different mechanisms play an important role in this infection in natural heterogeneous populations, indicating that NO, TNF-α and Th1 cytokines are involved in the infection control.
Keywords: Biozzi mice; Immune response; Mycobacterium bovis; Bacteria (microorganisms); Human immunodeficiency virus; Murinae; Mus; Mycobacterium bovis BCG; Mycobacterium tuberculosis